Photoionization of atomic scandium in the 3p->3d resonance region - (:unkn) unknown (EDITIONS PHYSIQUE, 1996)
Many-body perturbation theory (MBPT) calculations of the photoionization cross-section of atomic Sc have been performed from threshold to 70 eV. We consider excitations from the 3p, 3d, and 4s subshells. Over a broad energy range, the 3P --> 3d resonances, which are split into a number of multiplets, dominate the cross-section. The interaction between the resonances and the 3p --> kd channels is significant. Good qualitative agreement with experiment is found.
Keywords: CROSS-SECTION